Active learning through projects in mathematics: a strategy for effective implementation of curriculum design - Arias-Albuja, María (2025)
This article analyzes the use of Project-Based Learning (PBL) as an active teaching strategy to strengthen mathematics teaching at the upper elementary and high school levels. This research arose from the need to align pedagogical practices with current curriculum design, promoting meaningful learning that transcends memorization and fosters the development of competencies. The objective of this work is to evaluate the effect of PBL on mathematics teaching within the Ecuadorian curriculum context, identify relevant teaching activities for its implementation, and design a methodological guide to support teachers in its application. The study adopted a mixed approach, with an interpretive perspective, combining qualitative and quantitative techniques. Data collection was conducted through surveys administered to 160 students and 30 teachers from different public and private educational institutions in Quito, Ecuador. The findings reveal that PBL is highly valued for its ability to generate contextualized and relevant learning, although it faces obstacles such as a lack of resources, limited time, and insufficient teacher training. PBL contributes to a better understanding of mathematical content by integrating it with real-life problems, in addition to enhancing skills such as critical thinking, collaboration, and problem-solving. Students prefer active methodologies that connect learning to their environment, which underscores the importance of reinforcing this approach through actions that mitigate its limitations.